Reported Motivations for and Locations of Healthy Eating Among Georgia High School Students. (May 2017) - Kumar, Gayathri S.; Bryan, Michael; Bayakly, Rana; Drenzek, Cherie; Merlo, Caitlin; Perry, Geraldine S.
ABSTRACT: BACKGROUND: Understanding how youth perceive eating healthy foods can inform programs and policies that aim to improve healthy eating. We assessed the reasons for and the most common locations of eating healthy foods among Georgia's (GA) high school (HS) students. METHODS: Using the 2013 GA HS Youth Risk Behavior Survey, we examined motivations for and locations of eating healthy foods by sociodemographic characteristics and daily fruit and vegetable intake. Weighted chi‐square tests were used to examine differences in responses for each perception. RESULTS: Nineteen percent of GA HS students consumed fruit ≥3 times/day and 11% consumed vegetables ≥3 times/day. The most frequently chosen response to motivations for eating healthy foods was the desire to be healthy (42%), followed by enjoying their taste (18%). The most likely location to eat healthy foods was at home (80%), followed by at school (13%). CONCLUSIONS: GA HS students are most motivated to eat healthy foods by the desire to be healthy and their enjoyment of the taste of healthy foods. Incorporating messages that align with students' motivations to eat healthy foods could be considered when developing promotional programs/policies targeting healthy eating.